1980
DOI: 10.1007/bf01869350
|View full text |Cite
|
Sign up to set email alerts
|

Action of glucosamine on acetylcholine-sensitive channels

Abstract: The action of glucosamine was studied on voltage clamped neurones of Aplysia, presenting an excitatory response to acetylcholine. Noise and relaxation experiments show that glucosamine increases the mean channel open time and reduces the amplitude of the elementary current associated with the acetylcholine response. Both effects are enhanced by hyperpolarization of the cell membrane. The results are interpreted by a model assuming glucosamine binding to open channels. This binding impedes the flow of permeant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…There seems no necessity to invoke such a complicated scheme to explain the present results. 414 CHANNEL BLOCKADE BY CHLORISONDAMINE Nature of the stable-blocked state Several studies have examined the effects of various permeant ions on channel lifetime and proposed the view that occupation of the lumen of ionic channels by an ion effectively hinders the normal closure of the channel (Marchais & Marty, 1980;Ascher, Marty & Neild, 1978b;Gage & Van Helden, 1979; reviewed by Steinbach, 1980). Similar observations have been made for the potassium channel of the squid axon and of frog muscle (Swenson & Armstrong, 1981;Stanfield, Ashcroft & Plant, 1981).…”
Section: Factors Influencing Recovery From the Blocked Conditionmentioning
confidence: 99%
“…There seems no necessity to invoke such a complicated scheme to explain the present results. 414 CHANNEL BLOCKADE BY CHLORISONDAMINE Nature of the stable-blocked state Several studies have examined the effects of various permeant ions on channel lifetime and proposed the view that occupation of the lumen of ionic channels by an ion effectively hinders the normal closure of the channel (Marchais & Marty, 1980;Ascher, Marty & Neild, 1978b;Gage & Van Helden, 1979; reviewed by Steinbach, 1980). Similar observations have been made for the potassium channel of the squid axon and of frog muscle (Swenson & Armstrong, 1981;Stanfield, Ashcroft & Plant, 1981).…”
Section: Factors Influencing Recovery From the Blocked Conditionmentioning
confidence: 99%
“…In addition, it has been reported that DGL reduces the elementary current amplitude and increases the mean channel open time [31]. Because DGL has a weak binding site in the channel itself, the channel cannot be closed [31].…”
Section: Discussionmentioning
confidence: 99%
“…Because DGL has a weak binding site in the channel itself, the channel cannot be closed [31]. Voltage-gated sodium channels, which are necessary for electrogenesis and nerve impulse conduction, can be dynamically regulated after nerve injury or peripheral inflammation and can play important roles in modulating neural excitability [32, 33].…”
Section: Discussionmentioning
confidence: 99%